Clients’ experiences in their first entry to the operating room: a descriptive phenomenological study - Nasim Alipour; Amir Jalali; Rostam Jalali; Alireza Khatony (Perioperative Medicine)
Abstract Background The unfamiliar atmosphere of the operating room, waiting for anesthesia, and the process of surgery and anesthesia are some of the factors causing fear and anxiety in patients. It leads to physical and psychological pressure on patients. Better understanding of patients’ feelings, beliefs, or fears and recording their experiences for optimal care after surgery is helpful. This study explains the experiences of clients in the first entry to the operating room. Methods This qualitative study was conducted using a descriptive phenomenological method. In this study, 17 patients who had the experience of entering the operating room for the first time as an elective surgery under general anesthesia over the last 6 months were purposefully selected as participants. Then, they underwent an in-depth and semi-structured interview. After conducting the interview, the participants’ statements were qualitatively analyzed using the seven-step Colaizzi method. During the steps of this study, Lincoln and Guba’s four reliable criteria were observed. Results By continuous analysis of interviews about patients’ experiences, 308 codes, 10 sub-themes, 6 primary themes, and 3 general themes were obtained. Themes included unpleasant emotions experienced, unpleasant atmosphere factors, and the induction of relaxation and hope. Conclusion Patients’ exposure to an unfamiliar place with new and unknown equipment, personnel with different clothing, stress, worry, psychosomatic reactions following stress, and annoying environmental factors can lead to an unpleasant experience for patients, if they are not managed. Also, the effective communication of the surgical team with the patients leads to reducing or removing the stress and complications caused by it.